2021
DOI: 10.21203/rs.3.rs-470715/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outlining the causes and effects of Algae bloom at Ghana’s West Coast

Abstract: The first incidence of algal bloom within Ghana’s west coast was recorded in 1993, however many years down the line, the growth is still persistent in her territorial waters. A lasting solution is yet to be found. This has therefore led to several social, economic and environmental problems in the affected regions. The study outlined the possible causes and effects of algal bloom within Ghana’s West Coast. The perception of the local people with regards to the causes was also investigated. The method used was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Use of planktivorous fish as contrast to piscivorous fish for elimination of blue green algae had been done in closed water body and open lake ecosystem as well. Around sixteen studies [31], found the successful elimination of algae blooms with silver carp and some studies observed no or adverse effect [32][33][34]. Certain studies lead to controversial situation on the use of silver carp for the management of phytoplankton that increase their number instead of ceasing them [35,36].…”
Section: Non-classical Biomanipulation: Use Of Planktivorous Fishmentioning
confidence: 99%
“…Use of planktivorous fish as contrast to piscivorous fish for elimination of blue green algae had been done in closed water body and open lake ecosystem as well. Around sixteen studies [31], found the successful elimination of algae blooms with silver carp and some studies observed no or adverse effect [32][33][34]. Certain studies lead to controversial situation on the use of silver carp for the management of phytoplankton that increase their number instead of ceasing them [35,36].…”
Section: Non-classical Biomanipulation: Use Of Planktivorous Fishmentioning
confidence: 99%